Finite element modelling of shape memory alloy based smart link composite satellite structure - Vasanthanathan, A.; Nagaraj, P.; Chandravadhana, C.; Vasiraja, N. (Journal of Structural Engineering, 2024)
This paper addresses the deployment mechanism of the composite satellite antenna structure with the actuated shape memory alloy (SMA) hinges. In this study, the antenna structure implemented in the GARUDA-1 Aces Satellite has been considered. The actual dimensions of the antenna structure are scaled down to the prototype and the model is designed with the PRO-E® Wildfire 3.0 software. The shape memory alloy wire is analyzed using the finite element modelling for the shape memory effect to achieve the shape recovery of the deployed antenna. In the finite element simulation, the shape memory effect is incorporated in the axisymmetric antenna structure and then the structure is deformed by applying the external load. In the present analysis, the deformed antenna structure is heated to the transition temperature of the shape memory alloy wire for the phase transformation and hence the fully deployed antenna structure is achieved through the deployment mechanism. The entire finite element calculations are carried out in this paper using the ANSYS®14.5 finite element software.